Osteoid osteoma of the capitate (case report) - Magomed M. Dokhov; Roman V. Oleshev; Yuliya I. Titova; Olga V. Matveeva (Гений oртопедии, 2022)
Introduction Osteoid osteoma (OO) is a rare bone pathology of the hand. OO localization and pain syndrome associated with it may present a challenging diagnosing problem as its symptoms are nonspecific and the X-ray pattern is unclear. Our research is aimed at presenting the findings of the clinical and instrumental examination, and the outcome of successive surgical management of a patient with OO of the capitate. Material and methods We examined a 46-year-old male patient to verify the diagnosis of OO; he had the ultrasonic examination of his hand soft tissues and joints, biplane radiography of the wrist joint, computed tomography (СТ), and magnetic resonance imaging (MRI) of his left hand. A 0.6-cm defect of the capitate bone along with its increased bone density was visible in the X-rays of the patient’s left hand. In CT and MRI images, a 0.65 × 0.65 cm and up to 0.45-cm deep marginal bone defect on the capitate dorsum was identified. A 0.55 × 0.45 cm loose bone fragment was also found at that level. The examination was followed up by surgical management that involved marginal excision and extraction of the nidus of the left capitate bone. Results The patient reported the absence of pain in his hand and the increase in the range of motion in his wrist joint right after the surgery. The check-up X-ray images after three months revealed the signs of bone remodeling in the area of surgical intervention. The capitate defect was not found. Discussion OO in the hand may resemble a grainy remodeling of the osseous structure. A comprehensive examination that includes CT and MRI is crucial for revealing this rare OO localization. Conclusion The atypical localization and the patient’s age unusual for the liaison challenge the diagnosis and provide for the wrong choice of the treatment strategy.